Impact of Competitive Strategies on Market Entry and Growth in Emerging Economies in Japan - Akemo, Aiko (International Journal of Strategic Management, 2023)
Purpose: The study sought to analyze the impact of competitive strategies on market entry and growth in emerging economies in Japan Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: the study on competitive strategies in emerging economies in Japan revealed that cost leadership strategies facilitated successful market entry, while differentiation strategies promoted long-term growth. Strategic alliances with local firms were crucial for overcoming barriers, and early entry provided a competitive edge. Adapting strategies to Japan's unique cultural and regulatory context was deemed essential for success in emerging markets. Unique Contribution to Theory, Practice and Policy: The study recommends fosters a win-win scenario where foreign firms can thrive, and the host economy benefits from increased investments and job opportunities. Developing local talent and transferring knowledge to the local workforce is crucial for long-term growth. Both firms and governments should invest in skill development programs and knowledge transfer initiatives. Firms should prioritize hiring and training local talent, while governments can incentivize such efforts through grants and tax incentives. This practice-policy collaboration ensures that emerging economies can benefit not only from the capital but also from the knowledge and expertise brought by foreign firms.